Метафори пам'яті в українській поезії періоду російсько-української війни - Лариса Кравець; Larysa Kravets; Kravec Larissza (Видавничий дім Дмитра Бураго, 2023)
Резюме. У статті на матеріалі українських поетичних текстів періоду сучасної російсько-української війни простежено се- мантичні зв’язки концепту ПАМ’ЯТЬ з іншими когнітивними утвореннями. З’ясовано, що цей концепт має складну і розгалу- жену структуру, численні зв’язки з іншими подібними одиниця- ми й множинні інтерпретації, утворюючи концептуальні поля. Встановлено, що в поетичних текстах актуалізовані різні види ПАМ’ЯТІ: індивідуальна й колективна, історична й культурна, національна й загальнолюдська. Через призму сучасних філософ- ських концепцій проаналізовано специфіку їх метафоричного вираження та реалізований у цій формі зміст. Обґрунтовано, що вживання метафор ПАМ’ЯТІ в мові українських поетичних текстів зазначеного періоду осмислене, відповідає авторським намірам і підпорядковане художнім завданням.

Abstract. The concept of memory is one of the most researched and variously interpreted both in art and in philosophy, therefore reliance on philosophical theories significantly deepens the linguistic study of it in the language of poetry. Scientific and artistic coverage of memory are certainly different, but at the same time they are not devoid of some common features, which is manifested, in one case, in the application of techniques traditional for art in the process of philosophical study, and in the other – in the actualization of philosophical ideas during the creation of images. Expression of the concept of memory in fiction often has a philosophical basis. In general, all fiction can be interpreted as a means of forming, preserving and transmitting memory. Modern poetic texts of the war period not only reflect reality, interpret it, but also appeal to memory, actualizing the corresponding concept. This concept has a complex and branched structure, numerous associative connections and multiple interpretations, forming conceptual fields. Different types of memory are depicted in the works. This is individual and collective memory, historical and cultural, national and universal. It is not always easy to differentiate the types of memory implemented in the text, as they are often intertwined and mutually conditioned. Poetic texts testify that individual memory is not opposed to collective memory, because individual memory is formed in society thanks to human connections and activity, and therefore is part of collective memory. At the same time, individual memory is a unique combination of individual and collective memories. Collective memory preserves the past, which determines the experience of the present and the creation of the future. However, the past also changes under the influence of the present, moreover, it can be present in the present only under the condition of active collective memory. The concept of memory reveals numerous connections with many other concepts, including city, home, grave, temple, household items, etc. Memory is a way of being of a person in culture and the world, a measure of his spirituality, a form of timeless existence. Memory in one form or another permeates all Ukrainian poetry of the war period, actualizing values, evoking diverse emotions, prompting reflection. Memory brings back the past, which shapes the present and models the future.
Metaphors of memory in ukrainian poetry during the Russian-Ukrainian war
Українська поезія періоду війни звертається до архетипних тем, торкається екзистенційних питань, зазирає в глибини людської психіки. Традиційні для літератури концепти постають в оновленій формі із збагаченим та поглибленим змістом. Це надзвичайно цінний матеріал для дослідників, адже за ним можна вивчати динаміку мовної картини світу і поетичної мови, розвиток художнього стилю та образних систем, закономірності змін у мистецтві у кризові часи.
Keywords: концепт пам'ять; метафора; образ; поетичний твір; мовна картина світу; мовотворчість